2016
DOI: 10.1371/journal.pone.0163995
|View full text |Cite
|
Sign up to set email alerts
|

Contrasting Influences of Geographic Range and Distribution of Populations on Patterns of Genetic Diversity in Two Sympatric Pilbara Acacias

Abstract: The influence of geographic range on species persistence has long been of interest and there is a need for a better understanding of the genetic consequences for species with restricted distributions, particularly with the increasing rate of global species extinctions. However, the genetic effects of restricted range are often confounded by the impacts of population distribution. We compared chloroplast and nuclear genetic diversity and differentiation in two acacias, the restricted, patchily distributed Acaci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

14
43
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(61 citation statements)
references
References 76 publications
14
43
2
Order By: Relevance
“…This lack of genetic structure is consistent with results of studies of other Pilbara plants where little genetic structure has been found, e.g. E. camaldulensis (Butcher et al., ), A. ancistrocarpa and A. atkinsiana (Levy et al., ). The lack of structure associated with substrate or vegetation association is in contrast to the high level of association found in phylogenetic analysis of a number of reptile and invertebrate groups (see Pepper et al., ) and habitat specificity observed in taxa in the T basedowii species complex (Anderson et al., ).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…This lack of genetic structure is consistent with results of studies of other Pilbara plants where little genetic structure has been found, e.g. E. camaldulensis (Butcher et al., ), A. ancistrocarpa and A. atkinsiana (Levy et al., ). The lack of structure associated with substrate or vegetation association is in contrast to the high level of association found in phylogenetic analysis of a number of reptile and invertebrate groups (see Pepper et al., ) and habitat specificity observed in taxa in the T basedowii species complex (Anderson et al., ).…”
Section: Discussionsupporting
confidence: 89%
“…() found that Pilbara populations of Callitris glaucophylla that are confined to the Hamersley Range were genetically distinct from non‐Pilbara populations providing evidence of confinement to microrefugia during the last glacial period. The widespread Acacia ancistrocarpa did not show a genetic signature of refugia in the Hamersley Range, but populations in the Range had greater genetic connectivity consistent with historical persistence and large effective population size (Levy et al., ). In contrast, an analysis of E. camaldulensis across Australia found limited diversity in Pilbara populations (Butcher, McDonald, & Bell, ).…”
Section: Discussionmentioning
confidence: 99%
“…This has been demonstrated in a few recent studies on plants and birds. Two comparative studies on plants find that semi-continuously or continuously distributed populations have lower genetic differentiation than patchily distributed populations (Levy et al, 2016; Llorens et al, 2017). Robin et al (2015) studied an entire community of montane birds of the Western Ghats in India and found, with a few exceptions, highest genetic differentiation in montane-restricted species while the widespread species showed no genetic differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…This has been demonstrated in a few recent studies on plants and birds. Two comparative studies on plants find that semi‐continuously or continuously distributed populations have lower genetic differentiation than patchily distributed populations (Levy et al, ; Llorens et al, ). Robin, Vishnudas, Gupta, and Ramakrishnan () studied an entire community of montane birds of the Western Ghats in India and found, with a few exceptions, highest genetic differentiation in montane‐restricted species, while the widespread species showed no genetic differentiation.…”
Section: Discussionmentioning
confidence: 99%